Asuhan Keperawatan Pada Ny. H dengan Post Partum Spontan dengan Pre-Eklampsia Berat di Bangsal Anyelir RSUD Banyudono Boyolali - Nirmawati, Yuni, Rina Ambarwati, S.Kep., Ns (2013)
Background of study: The birth of a baby constitutes main priority. There several problems that triggers a mother become anxious and afraid within containing and gave birth to a baby. Problems which it often occurs in the mother gave birth to is preeclampsia. Figures incidence of preeclampsia is including the one that causing a mother died in the process of and after childbirth. Objectives of the study: To know the nursing care on patients post spontaneous partum in first day with severe preeclampsia indication, covering assessment, intervention, implementations, and evaluation. The results of: After nursing care during 3 x 24 hours it is obtained outcomes patient's agonies already diminished of scale 5 become 2, infection does not happen, less knowledge overcame, as well as the extenuation also is resolved. Conclusion: Diagnosis which found on cases of post spontaneous partum first day with severe preeclampsia indication in Mrs. H is the acute agonies relate with agents injury-physical, high risk infection associates with trauma system, less knowledge about breast care relates to lack of information, weariness in touch with anemia. All of problem nursing has already resolved. On the application of nursing care post spontaneous partum with severe preeclampsia Mrs. H does not found to nursing problem who do not or yet resolved.